Problem Posing in Prospective Primary School Teacher: Perspective Commognitive - Pratiwi, Enditiyas; Nanna, A.Wilda Indra; Rahmatina, Desi; Zayyadi, Moh; Kholid, Muhammad Noor (Universitas Teknokrat Indonesia, 2024)
This research explores the problem-posing abilities of students, especially prospective primary school teachers, which are demonstrated through problem-posing creativity produced through worksheets. In exploring students' problem-posing abilities, descriptive research with a qualitative approach was used. The subjects in the research were prospective primary school teacher students who had taken a number concept course which was chosen based on the problem-posing strategy that emerged after solving the given problem. Furthermore, subjects were interviewed in-depth to find out cognitive by looking at four indicators, namely word use, visual mediator, narrative and routine. The research results showed that there were no subjects with imitation strategies and subjects with reformulation strategies and reconstruction strategies did not give rise to problem-posing using visual mediators. This is because the subject is not used to problem-posing mathematical models in the form of diagrams or symbols.